Creating a Technopreneurship-Based Life Skills Education Model with Methods of Project-Based Learning - Suminar, Tri; Sutarto, Joko; Siswanto, Yudi; Cahyani, Arini Dwi (Aptisi Transactions On Technopreneurship (ATT), 2025)
Low interest in sustainable learning among adult learners in the Paket C equivalency education program stems from learning materials that do not align with the needs for work skills or entrepreneurship. This research aims to develop a technopreneurship-based life skills education model using a Project-Based Learning (PjBL) method to enhance IT-based entrepreneurial skills, strengthen competitiveness, and instill character values in students. The study adopts the ADDIE model within the Research and Development (R&D) framework. The research population consists of adult dropout learners enrolled in the Paket C equivalency program implementing the independent learning curriculum in 2023. Data collection methods include in-depth interviews, observations, documentation, and Google Form questionnaires. Expert and practitioner validation tests of the model were conducted using semi-open questionnaires. Data analysis involved interactive models, descriptive statistics, N-gain, and the Wilcoxon test. The results indicate that the conceptual model was designed by incorporating graduate competency standards, content standards, and process standards, using a PjBL approach. Validation tests by experts and practitioners confirmed that the model is valid and applicable in learning practices. The trial results of the hypothetical model showed that the technopreneurship-based life skills education model effectively improves entrepreneurial skills and supports character development in line with the Pancasila student profile. This model can increase students motivation to complete the equivalency program and achieve graduation.